A study of EMG signal during one arm weight-lifting - Mohd Amir Abdul Rahman (Universiti Malaysia Perlis, 2008)
Electromyography (EMG) is the study of muscle function through analysis of the electrical signal produced during muscular contraction. EMG involves detection, amplification, recording, analysis, and interpretation of electrical signals. Surface EMG uses bipolar surface electrodes placed on the surface of the skin to detect voltage differences due to asynchronous activation of motor units. Therefore, the surface EMG actually provides indirect information about levels of motor unit activity. The purpose of this study was to investigate an EMG signal in one arm region during lifting weight. Some parameters were investigated to see the relation with the EMG. There are relation between gender, age, handedness and body weight. Besides, the determination of fatigue to time was also investigated. Ten healthy males and females participated in the study. The weight-lifting was considered only for one arm side for each time.